Profil Asam Lemak Minyak Ikan Belanak (Chelon planiceps) Sebagai Sumber Omega-3 Asal Desa Lembo Kabupaten Konawe Utara - Nurull - Hikmah; Nita Trinovitasari; Nurramadhani A.Sida; Nurramadhani A. Sida; Irvan Anwar; Nurul Aliah Fadhilah; Irnawati (Pharmaceutical and Biomedical Sciences Journal (PBSJ), 2025)
Ikan Belanak (Mullet) is a small pelagic fish that lives in shallow coastal waters. This type of fish lives in the coastal area of Lembo Village, North Konawe Regency. The objective of this study was to characterize physicochemicals and determine the fatty acid profile of mullet oil, which is a source of fish oil that contains unsaturated fatty acids that are beneficial to health. The reflux process is used to remove mullet flesh, which yields fish oil. The findings demonstrated that the physicochemical properties of mullet oil varied. These properties included the acid number, peroxide number, iodine number, and saponification number, which were, respectively, 0.81 mg KOH/g, 8.30 meqO2/kg, 50.98 I2/100 g, and 109.07 mg KOH/g. The fatty acid profile of mullet oil is dominated by palmitic acid, cis-9-oleic acid and DHA. Based on the test results, mullet oil can be used as edible oil according to SNI and IFOS standards.